(untitled) (مجلة إحالات, 2025)
استحوذت مسألة الطّبع والصّنعة على اهتمام النُّقاد والبلاغيين العرب القدامى، لذا أسهبوا الحديث عنها في مختلف تواليفهم وعَديدِ مصنّفاتهم النّقديّة – النظرية منها والتَّطبيقية – بُغية تفسيرها ذلك التّفسير الذي لم يسلم عندهم من بعض الغموض والضَّبابية، نظراً لتفاوت تصَوُّرهم لها وتبايُنِ الآراء ووجهاتِ النَّظر حولها. هذا ولقد عُني النُّقاد المغاربة بهذه القضيَّة التي تدخُلُ ضمن سياقات صِناعة الشعر وتشكيله انطلاقاً من مفهوم العملية الإبداعيّة، لذلك ألفيناهم هرعوا يوضِّحون جوانبها، ويُبلْورونَ طروحاتِ وآراء سابقيهم لها، مُتَّبِعِيْنَ في ذلك منهجاً نقديَّاً متكاملاً، يسودُه حسنُ التقسيم والتَّطبيق، وعمق الفهم والمناقشة، محاولين التميُّـزَ والتَّفرُّد والجِدَّة ما أمكن. من أجل ذلك عقدنا هذه الورقة البحثيّة التي تحاول رصد معالم هذه المسألة النَّقديّة الهامّة، ومناقشة آليَّاتها الإجرائيَّة، ومنطلقاتها المعرفيَّة، اِستناداً على أهمِّ تلك المفاهيم النَّقدية والبلاغية التي رافقت وعُنيت بعملية الإبداع الشعري من منظور ناقدنا المغاربي " ابن شرف القيرواني ". The issue of printing and manufacturing has attracted the attention of the old Arab critics and rhetoric, so they elaborated on them in their various combinations and many of their critical works - both theoretical and practical - in order to interpret them, which did not escape some ambiguity and ambiguity, due to their differing perceptions and opinions. Moroccan critics are concerned with this issue, which falls within the contexts of the hair industry and its formation from the concept of the creative process, so two thousand rushed to clarify its aspects, and elaborate the views and opinions of their predecessors, following this approach Critically integrated, dominated by good division and application, and the depth of understanding and discussion, trying to excellence, individuality and novelty as possible. For this reason we held this research paper, which attempts to monitor the features of this critical issue, and discuss its procedural mechanisms, and its cognitive perspectives, based on the most important critical and rhetorical concepts that accompanied and concerned the process of poetic creativity from the perspective of the Maghreb critic "Ibn Sharaf Kairouani."